Realization of an Asymmetric Interdigitated Electrochemical Micro-Capacitor Based on Carbon Nanotubes and Manganese Oxide. Issue 10 (1st January 2015) - Dinh, Ty Mai; Mesnilgrente, Fabien; Conédéra, Véronique; Kyeremateng, Nana Amponsah; Pech, David
Abstract : Asymmetric interdigitated micro-supercapacitors with high resolution, dedicated to energy storage in embedded micro-systems, are fabricated using a simple micro-fabrication process based on the inkjet printing and electrolytic deposition techniques. The process is optimized to realize a carbon nanotubes (cathode)/manganese oxide (anode) hybrid micro-device with a resolution of 100 μm. The cell capacitance reaches a value of 2.4 mF.cm −2 . Moreover, the use of the asymmetric configuration allows extending the working voltage of the device from 1 V to 1.8 V in an aqueous solution.